Synergies and Trade-Offs in Reducing Impacts of Unconventional Oil and Gas Development on Wildlife and Human Health. (30th March 2022) - Deziel, Nicole C; Shamasunder, Bhavna; Pejchar, Liba
Abstract: With growing evidence of widespread health and environmental impacts from oil and gas activity, localities and states are beginning to develop protective measures. Interdisciplinary approaches that integrate across human, wildlife, domesticated animal, and land health are likely to provide more just and comprehensive solutions than would be possible with siloed approaches. However, this is not common practice, and there is little guidance on how to apply such a strategy. In the present article, we summarize the state of knowledge on the impacts of terrestrial unconventional oil and gas development from the fields of ecology and public health. We then discuss synergies and trade-offs regarding impacts and mitigation strategies emerging from these two literatures. Finally, we provide recommendations for research and practice to fill knowledge gaps and better inform integrated decision-making to achieve multiple benefits and minimize impacts on human, wildlife, domesticated animals, and land health from energy development.